Sistem Rekomendasi Pemilihan Jenis Lensa Kacamata Menggunakan Metode Knowledge Based Recommendation (Studi Kasus : Optik Wiratama Kacamata 2) - Ulhaq, Ahmad Dia; Hartanti, Dwi; Sari, Aprilisa Arum (Universitas Indraprasta PGRI Jakarta, 2025)
The main problem that customers often face in choosing eyeglass lenses is the lack of information that suits the user's specific needs, such as eye complaints, daily activities, and lens feature preferences. This study aims to build a recommendation system for selecting eyeglass lenses using the Knowledge-Based Recommendation approach with the Constraint-Based method. The system development methodology uses the Agile Software Development model, with iterative stages that allow for periodic system evaluation. Data were obtained through interviews with customers and staff of Optik Wiratama Kacamata 2, as well as direct observation of user needs. This system was built web-based with the PHP programming language and the Laravel framework. The system test results showed a level of recommendation accuracy with a recall value of 100% and an average precision of 89.16%, indicating that the system is able to provide relevant lens recommendations that suit user needs. This study contributes to providing digital solutions that help decision-making in selecting eyeglass lenses in a personal and efficient manner.